The Concept of Mahdī in Shī'ī Theology - Nurul Fajri (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
The Shī’ī eschatological doctrine encompasses the belief in the Imām Mahdī, or the Hidden Imām, who will reemerge at the end of time as a savior. This savior is anticipated to establish socio-political justice and equity, leading to a peaceful life grounded in Islamic teachings. In essence, the Imām Mahdī is believed to bring about an ideal religious society.